A strategy for successive feedstock reuse to maximize photo-fermentative hydrogen production of Arundo donax L. (June 2021) - Jiang, Danping; Yue, Tian; Zhang, Zhiping; He, Chao; Jing, Yanyan; Lu, Chaoyang; Zhang, Huan; Chen, Zhou; Zhang, Quanguo
Graphical abstract: Highlights: Arundo donax L. was reused 4 times to maximize the hydrogen yield. A 2-fold hydrogen yield was achieved after the successive 4-batch PFHP. 1st batch obtained the maximum hydrogen yield and hydrogen production rate. 2nd batch gave the maximum substrate conversion efficiency of 96.5%. No significant difference in hydrogen yield of the last 3 batches PFHP. Abstract: This study proposed a strategy to maximize the hydrogen yield by reusing feedstock of Arundo donax L. For this purpose, a successive 4-batch photo-fermentative hydrogen production (PFHP) was carried out to test the strategy. About 50% of total hydrogen yield was additionally obtained by reusing the Arundo donax L for successive 4 times in comparison to single 1st batch (161.4 mL/U. cell dry weight). In addition to the highest hydrogen yield, the maximum hydrogen production rate (6.0 mL/U. cell dry weight /h), and the highest volatile fatty acids (VFAs) concentration (32 mM) were also obtained from the 1st batch, while the 2nd batch gave the maximum substrate conversion efficiency (96.5%). Moreover, a positive relationship between the sum of acetic and butyric acids with hydrogen yields was observed. This strategy would help in enhancing hydrogen yield that coupled with cost reduction for biohydrogen production.